Прагматические аспекты российского медийного словотворчества - Рацибурская, Лариса (Studia Rossica Posnaniensia, 2019)
The article focuses on the specificity of pragmatic aspects of innovations survey in mass media. Special attention is paid to the functional peculiarities of such phenomena as evaluativeness and expressiveness, word-building play based on precedence and polycode innovations. The issues of communicative methods of recipient impact in the sphere of media word creation are also analyzed.